Acupuncture for Managing Cancer-Related Insomnia: A Systematic Review of Randomized Clinical Trials. (June 2017) - Choi, Tae-Young; Kim, Jong In; Lim, Hyun-Ja; Lee, Myeong Soo
Background . Insomnia is a prominent complaint of cancer patients that can significantly affect their quality of life and symptoms related to sleep quality. Conventional drug approaches have a low rate of success in alleviating those suffering insomnia. The aim of this systematic review was to assess the efficacy of acupuncture in the management of cancer-related insomnia. Methods . A total of 12 databases were searched from their inception through January 2016 without language restriction. Randomized controlled trials (RCTs) and quasi-RCTs were included if acupuncture was used as the sole intervention or as an adjunct to another standard treatment for any cancer-related insomnia. The data extraction and the risk of bias assessments were performed by 2 independent reviewers. Results . Of the 90 studies screened, 6 RCTs were included. The risk of bias was generally unclear or low. Three RCTs showed equivalent effects on the Pittsburgh Sleep Quality Index and 2 RCTs showed the similar effects on response rate to those of conventional drugs at the end of treatment. The other RCT showed acupuncture was better than hormone therapy in the numbers of hours slept each night and number of times woken up each night. The 3 weeks of follow-up in 2 RCTs showed superior effects of acupuncture compared with conventional drugs, and a meta-analysis showed significant effects of acupuncture. Two RCTs tested the effects of acupuncture on cancer-related insomnia compared with sham acupuncture. One RCT showed favourable effects, while the other trial failed to do so. Conclusion . There is a low level of evidence that acupuncture may be superior to sham acupuncture, drugs or hormones therapy. However, the number of studies and effect size are small for clinical significance. Further clinical trials are warranted.